Reassembly of functionally intact environmental DNA-derived biosynthetic gene clusters - Kallifidas, Dimitris (2012)
Only a small fraction of the bacterial diversity present in natural microbial communities is regularly cultured in the laboratory. Those bacteria that remain recalcitrant to culturing cannot be examined for the production of bioactive secondary metabolites using standard pure-culture approaches. The screening of genomic DNA libraries containing DNA isolated directly from environmental samples [environmental DNA (eDNA)] provides an alternative approach for studying the biosynthetic capacities of these organisms. One drawback of this approach has been that most eDNA isolation procedures do not permit the cloning of DNA fragments of sufficient length to capture large natural product biosynthetic gene clusters in their entirety. Although the construction of eDNA libraries with inserts big enough to capture biosynthetic gene clusters larger than ~40 kb remains challenging, it is possible to access large gene clusters by reassembling them from sets of smaller overlapping fragments using transformation associated recombination (TAR) in Saccharomyces cerevisiae. Here we outline a method for the reassembly of large biosynthetic gene clusters from captured sets of overlapping soil eDNA cosmid clones. Natural product biosynthetic gene clusters reassembled using this approach can then be used directly for functional heterologous expression studies.